2011
DOI: 10.1038/ijo.2011.86
|View full text |Cite
|
Sign up to set email alerts
|

Replication of 13 obesity loci among Singaporean Chinese, Malay and Asian-Indian populations

Abstract: Objective: Recent genome-wide association studies (GWAS) have identified 38 obesity-associated loci among European populations. However, their contribution to obesity in other ethnicities is largely unknown. Methods: We utilised five GWAS (N ¼ 10 482) from Chinese (three cohorts, including one with type 2 diabetes and another one of children), Malay and Indian ethnic groups from Singapore. Data sets were analysed individually and subsequently in combined meta-analysis for Z-score body-mass index (BMI) associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
55
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(61 citation statements)
references
References 20 publications
4
55
2
Order By: Relevance
“…CNV loci overlapping LPA and JAK2 were observed with nonsignificant p-values. In the association stage, other well-established risk loci such as ATP2B1, FTO, MC4R, PPYR1, ST7L-CAPZA1, FIGN-GRB14, EN-PEP, NPR3, and TBX3 that were observed in previous GWAS or CNV studies (Sha et al, 2009;Levy et al, 2009;Newton-Cheh et al, 2009;Kato et al, 2011;Frayling et al, 2007;Loos et al, 2008;Glessner et al, 2010;Dorajoo et al, 2011) were not observed in our current study. There are some potential reasons for why these loci were not significantly observed in our study.…”
Section: Discussioncontrasting
confidence: 44%
“…CNV loci overlapping LPA and JAK2 were observed with nonsignificant p-values. In the association stage, other well-established risk loci such as ATP2B1, FTO, MC4R, PPYR1, ST7L-CAPZA1, FIGN-GRB14, EN-PEP, NPR3, and TBX3 that were observed in previous GWAS or CNV studies (Sha et al, 2009;Levy et al, 2009;Newton-Cheh et al, 2009;Kato et al, 2011;Frayling et al, 2007;Loos et al, 2008;Glessner et al, 2010;Dorajoo et al, 2011) were not observed in our current study. There are some potential reasons for why these loci were not significantly observed in our study.…”
Section: Discussioncontrasting
confidence: 44%
“…11,39 The TMEM18 and GNPDA2 associations have also been validated in East Asian studies. 40,41 Figure 1. Effects of rs9939609 and rs6548238 on obesity-related indices for overall sample, boys and girls.…”
Section: Discussionmentioning
confidence: 99%
“…GWAS identified obesity-associated genes such as FTO, MC4R, GNPDA2, TMEM18, QPCTL/GIPR, BDNF, ETV5, MAP2K5/ SKOR1, SEC16B and TNKS/MSRA have been shown to be associated with obesity risk in Singaporean Asian-Indian populations [88]. In addition, GWAS in Asian Indians have reported strong associations of variants near MC4R genes with insulin resistance and several obesity-related quantitative traits [89].…”
Section: Indian Perspective Of Obesity Geneticsmentioning
confidence: 99%